A green methodology for the determination of cocaine in camouflaged samples. Issue 16 (13th April 2023) - Gallart-Mateu, D.; Gallardo, A.; Garrigues, S.; de la Guardia, M.
Abstract : The procedure developed, based on an ultrasound probe assisted extraction followed by DFATR-MIR analysis, offers a fast, simple and efficient way for the determination of cocaine camouflaged in different types of solid samples. Abstract : A methodology based on the ultrasound-assisted extraction with ethanol and the dry film attenuated total reflectance infrared spectroscopy (DF-ATR-FTIR) measurement of extracts has been developed for a fast evaluation of non-conventional ("exotic") solid-sized cocaine samples. The method provides quantitative results in less than three minutes with a limit of detection in the solid sample of 1.6 μg g −1 of cocaine with a variation coefficient lower than 7%. Results found for seized samples of different natures were compared with those obtained by a reference gas chromatography method and the greenness of the whole proposed procedure was evaluated and compared using the analytical eco-scale, green analytical procedure index (GAPI), and analytical greenness metric (AGREE). The green evaluation of the proposed methodology provided green scores by considering different evaluation criteria.